Learning experiences in training processes. Case of apprentices from a training center in the Caldas regional - Erazo Mu´ñoz, Pablo Andrés
The perception of the apprentices of a training center of SENA Caldas regional regarding the learning experiences in the development of the training program and their passage through the entity after at least one academic term has elapsed is presented, with the projection that the results may contribute to the implementation of actions by different institutional actors to improve the teaching-learning process, both in the improvement of the pedagogical practices of the instructors and in the satisfaction and expectations of the apprentices of the training center. The research methodology has a mixed approach. For the construction of the applied instrument, educational theories and institutional regulations were taken into account and focus groups were conducted with institutional experts, in addition to factorial analysis and reliability tests. The target population of the study was 467 enrolled apprentices belonging to 29 technological, technical and operative level programs in the second quarter of the year 2023.  It was concluded that: there is a moderate correlation between the application of active techniques and didactics, the accompaniment in the execution of the training, the motivation of the apprentice and the satisfaction with the training process of the apprentices of the training center.